2014
DOI: 10.1021/jp5086679
|View full text |Cite
|
Sign up to set email alerts
|

Similar Strength of the NH···O and NH···S Hydrogen Bonds in Binary Complexes

Abstract: The weakly interacting complexes of dimethylamine with dimethyl ether (DMA-DME) and with dimethylsulfide (DMA-DMS) have been detected in the gas phase using Fourier transform infrared spectroscopy at room temperature. The observed redshift of the fundamental NH-stretching frequency was found to be extremely small with only 5 and 19 cm(-1) for DMA-DME and DMA-DMS, respectively. The experimentally determined integrated absorbance has been combined with a calculated oscillator strength to determine an equilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 63 publications
1
52
0
Order By: Relevance
“…They used a range of values that have been previously suggested for  b and  2  b (0.002 <  b < 0.034 au; 0.024 <  2  b < 0.139 au) to identify and characterize O⋯H(-C) hydrogen bonding in molecular complexes [66]; however, as we will show below, these may indeed be a useful guide, but should not be treated as a prerequisite for the identification of hydrogen bonding in chemical systems since non-covalent interactions, in general, do not have strict boundaries [42,43,46,58]. We will also demonstrate that because of its stringent criteria QTAIM sometime fails to identify weakly bound and van der Waals interactions in chemical systems [67][68][69][70][71]; this is the reason we employed the RDG-NCI approach to investigate the details of the bonding topologies involved.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…They used a range of values that have been previously suggested for  b and  2  b (0.002 <  b < 0.034 au; 0.024 <  2  b < 0.139 au) to identify and characterize O⋯H(-C) hydrogen bonding in molecular complexes [66]; however, as we will show below, these may indeed be a useful guide, but should not be treated as a prerequisite for the identification of hydrogen bonding in chemical systems since non-covalent interactions, in general, do not have strict boundaries [42,43,46,58]. We will also demonstrate that because of its stringent criteria QTAIM sometime fails to identify weakly bound and van der Waals interactions in chemical systems [67][68][69][70][71]; this is the reason we employed the RDG-NCI approach to investigate the details of the bonding topologies involved.…”
Section: Methodsmentioning
confidence: 91%
“…Unequivocally, the bcp is the point where one finds no difference between QTAIM and RDG. elucidated in several recent studies by the Kjaergaard group [67][68][69][70][71], in which it was shown that the experimentally-determined weakly bound and van der Waals interactions in molecular systems can be successfully identified and characterized by RDG-NCI, which may or may not be identified with QTAIM due to its stringent criteria.…”
Section: A Reduced Density Gradient (Rdg) Description Of Non-covalentmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22] With this method, equilibrium constants of complex formation are determined from the definition of the equilibrium constant…”
Section: Introductionmentioning
confidence: 99%
“…The stability of these complexes are indicated by their equilibrium BE, −7.07 kcal/ mol (Scheme 2a) and −7.60 kcal/mol (Scheme 2b), shown in Table 3, which are consistent with previous studies. 59,60 The BE for SO 2 adsorption at the amine site for the various structures shown in Scheme 1 were compared at the B3LYP/6-31G** and 6-31+G* levels and are reported in Table 3.…”
Section: Introductionmentioning
confidence: 99%